Today's Technician: Classroom Manual for Automatic Transmissions and Transaxles - Erjavec Jack (Thomson Delmar Learning, 2006)
This Classroom Manual and Shop Manual set has been newly revised to keep pace with industry trends and the needs of automotive education programs across the country. Its complete, technician-oriented coverage will lead users to mastery of all of the design, construction, troubleshooting techniques, and service procedures required to enter the workplace. The Classroom Manual begins with an important introduction to drive train basics, the Shop Manual with an intro to safety. This is followed immediately by a review of directly relevant electricity/electronics principles, plus more opportunities to gain practice in using scanners and oscilloscopes to develop critical thinking skills, diagnose problems, and make effective repairs. Today's Technician: Automatic Transmissions and Transaxles, 4th Edition also features an introduction to continuously variable transmissions (CVT), up-to-the-minute coverage of drivelines for front-wheel drive (FWD) and four-wheel drive (4WD) vehicles, and the latest information on today's high-tech electronic controls and automatic shifting devices.